Reversing the endowment effect by empowering buyers and sellers. (10th September 2018) - Chan, Eugene; Saqib, Najam
Abstract : Purpose: The endowment effect is well-established in economics, psychology and marketing where sellers place a higher value on a good than buyers. One potential moderator, namely, power is explored. The authors predicted that feeling powerful can reverse the effect, making buyers place a higher value on a good than sellers. Design/methodology/approach: The authors manipulated power to assess the effects on the valuation of three different products (keychain, gift card and iPhone case). They also assessed participants' focus on parting with the good (money), which is a loss, and receiving money (the good), which is a gain, for sellers (buyers). Findings: Feelings of power reduced sellers' prices but they increased buyers'. Crucially, the authors observed the endowment effect, but only under conditions of low power. When participants had high power, the effect reversed, with buyers placing a higher value on the good under transaction than sellers. Process data indicated that powerful buyers and sellers focused on what they gained and less on what they lost, compared to powerless buyers and sellers. Research limitations/implications: The authors link the construct of power with the endowment effect, showing that the former can moderate the latter. Certainly, the endowment effect is well-established, but there are moderators and boundary conditions that warrant consideration. Practical implications: The results suggest a case where the market may clear, where buyers value a consumer product more than sellers, and thus buyers would likely accept the offer made by sellers. Originality/value: The authors are the first to link the power literature with the endowment effect. They also show a possible moderator for the well-established endowment effect.